Issues raised by the treatment of bullying in the regulations and protocol of the Basque Country - Cadenas García, María Isabel (Avances en Supervisión Educativa, 2020)
This work addresses the study of the treatment of bullying in the regulations and protocol of the Basque Country with the intention of providing some guidance to the problems raised by its application. In particular, it asks whether the protocol applies only in public centers or also in private centers and whether the actions covered by it are understood to constitute the prior information provided for in Law 39/2015, of 1 October. Is also discusses the possibility to access the actions that constitute this prior information, how the actiones referred to in the protocol should be carried out, the deadline for holding the first meeting under the protocol, tha possibility to record the meetings that constitute actiones provided for in the protocol and the applicability of the principles and guarantees of the administrative procedure to these actiones provided for in the protocol
Keywords: bullying; protocol; public centers; private centers; prior information; access to information; recording; deadline; guarantees